Symmetry of the pupillary light reflex and its relationship to retinal nerve fiber layer thickness and visual field defect - Dolly S. Chang (2018)
Purpose. To assess the relationship between the pupillary light reflex (PLR) and visual field (VF) mean deviation (MD) and retinal nerve fiber layer (RNFL) thickness. Methods. A total of 148 patients with glaucoma (mean age 67±11, 49% female) and 71 controls (mean age 60±10, 69% female) were included in this study. Using a pupillometer, we recorded and analyzed pupillary responses at varied stimulus patterns (full field, superonasal and inferonasal quadrant arcs). We compared the responses between the two eyes, compared responses to stimuli in the superonasal and inferonasal fields within each eye, and calculated the absolute PLR value of each individual eye. We assessed the relationship among PLR, MD, and RNFL thickness using the Pearson correlation coefficient. For analyses performed at the level of individual eyes, we used multilevel modeling to account for between-eye correlations within individuals. Results. For every 0.3 log unit difference in between-eye asymmetry of PLR, therewas an average 2.6-dB difference in visual field MD (correlation coefficient R = 0.83, P < 0.001) and a 3.2-lm difference in RNFL thickness between the two eyes (R=0.67, P<0.001).Greater VF damage and thinner RNFL for each individual eye were associated with smaller response amplitude, slower velocity, and longer time to peak constriction and dilation after adjusting for age and sex (all P < 0.001). However, within-eye asymmetry of PLR between superonasal and inferonasal stimulation was not associated with corresponding within-eye differences in VF or RNFL. © 2013 The Association for Research in Vision and Ophthalmology, Inc.